Aspek Hukum Sertipikat Elektronik Dalam Sistem Pendaftaran Tanah Di Indonesia - Nizam Zakka Arrizal; Muhammad Ali Fauzi (Universitas Merdeka Madiun, 2023)
Land is a natural resource that is very important for human life, both directly and indirectly, directly such as being used as a place to live, to grow crops, to as an investment business. The importance of the function of the role of land requires strict regulations governing land use in order to avoid things that deviate. Land certificates are also required as proof of land ownership. Current technological developments make it easier for humans in all their activities, in the land sector now land certificates have undergone a change from what were originally in the form of physical documents to now electronic ones. This study discusses the legal aspects of electronic certificates in the land registration system in Indonesia. The method used is the normative juridical method, namely library law research which is carried out by examining library materials or mere secondary data. The results of the study show that Electronic Land Certificates are certificates issued in the form of electronic documents using an electronic system. The legal policy of mandatory electronic land certificates Land Registration in Indonesia is a regulation issued by the Ministry of ATR/Ka.BPN to improve services in the land sector in order to provide legal certainty and legal protection for owners.